Rapid deployment aortic valve replacement in a minimal access setting: intermediate clinical and echocardiographic outcomes. (6th February 2018) - Schlömicher, Markus; Taghiyev, Zulfugar; AlJabery, Yazan; Haldenwang, Peter Lukas; Zumholz, Michael; Sikole, Magdalena; Useini, Dritan; Naraghi, Hamid; Moustafine, Vadim; Bechtel, Matthias; Strauch, Justus Thomas
Abstract: OBJECTIVES: Transcatheter procedures have overtaken conventional operations in Germany. Considering that this is a highly competitive field, a rate of 25% for minimal access aortic valve replacement seems to be disappointingly low. One way to promote minimal access techniques is through the systematic use of rapid deployment valves. METHODS: A total of 143 patients underwent rapid deployment aortic valve replacement via upper right hemisternotomy between March 2012 and September 2015. All patients were followed up annually. Echocardiographic assessment of the valve was performed after 12 months. The cumulative follow-up time was 275.2 patient-years. The median follow-up time was 1.9 years. RESULTS: The mean age was 76.4 ± 6.2 years, and the mean logistic EuroSCORE was 11.0 ± 4.3%. Early all-cause mortality was 2.8% ( n  = 4). Actuarial survival after 1 year was 91.6 ±  2.4%, and after 3 years, it was 84.4 ± 3.6%. Mean transprosthetic gradient after 12 months was 10.3 ± 3.8 mmHg. New onset of higher grade paravalvular leakage did not occur during the follow-up period. Perioperatively, higher grade paravalvular leakage (aortic insufficiency  >1 + ) occurred in 2 cases (1.4%) . CONCLUSIONS: Rapid deployment aortic valve replacement can be performed safely in a minimal access setting with low complication rates and good haemodynamic results. Therefore, rapid deployment valves are a relevant option in minimal access surgery.